PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN PT. SUMBER ALFARIA TRIJAYA TBK - Sarahdillah Alfianti; Endah Dewi Purnamasari; Emilda Emilda (Jurnal Manajemen, 2023)
This study discusses the influence of organizational culture and job satisfaction on organizational citizenship behavior at PT Sumber Alfaria Trijaya Tbk. The purpose of this research is to find out whether there is a positive influence of organizational culture on organizational citizenship behavior, to determine the positive effect of job satisfaction on organizational citizenship behavior, and to find out the positive effect of job satisfaction on organizational citizenship behavior. This research is quantitative with a questionnaire as a data collection tool. Questionnaires were distributed to 90 employees at PT Sumber Alfaria Trijaya, Tbk. A total of 90 questionnaires were returned, and were analyzed using SPSS 25 software. The results of this study prove that there is a significant effect of job satisfaction on organizational citizenship behavior partially, there is a significant effect of job satisfaction on organizational citizenship behavior partially and simultaneously.